2012
DOI: 10.1182/blood-2012-02-410712
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment in vitro with Nutlin, a small-molecule antagonist of MDM2, and pegylated interferon-α 2a specifically targets JAK2V617F-positive polycythemia vera cells

Abstract: Interferon (IFN-␣) is effective therapy for polycythemia vera (PV) patients, but it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
(70 reference statements)
0
45
0
Order By: Relevance
“…Because type I interferons (IFN) target JAK2 V617F + progenitors in PV through activation of MAPK and STAT1, thereby increasing TP53 transcription, the combination of IFN with MDM2 inhibitors, which prevent the degradation of TP53, provides an opportunity to induce TP53-dependent apoptosis [170]. Indeed, combination treatment with IFN and the MDM2 antagonist Nutlin-3 triggered apoptosis in PV CD34 + cells and inhibited proliferation of these cells to a greater extent than normal CD34 + cells [170]. The combination also reduced the proportion of JAK2 V617F progenitors in PV patients.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because type I interferons (IFN) target JAK2 V617F + progenitors in PV through activation of MAPK and STAT1, thereby increasing TP53 transcription, the combination of IFN with MDM2 inhibitors, which prevent the degradation of TP53, provides an opportunity to induce TP53-dependent apoptosis [170]. Indeed, combination treatment with IFN and the MDM2 antagonist Nutlin-3 triggered apoptosis in PV CD34 + cells and inhibited proliferation of these cells to a greater extent than normal CD34 + cells [170]. The combination also reduced the proportion of JAK2 V617F progenitors in PV patients.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…The combination also reduced the proportion of JAK2 V617F progenitors in PV patients. Combination treatment of PV and primary MF CD34 + cells, followed by transplantation into immunodeficient mice, decreased the extent of donor-derived chimerism as well as the JAK2 V617F allele burden, suggesting that such combinatorial approaches may deplete MPN hematopoietic stem cells [170]. The clinical candidate MDM2 antagonist Idasanutlin is currently in a phase I trial in patients with PV or ET, with a provision for adding pegylated IFN in subjects without or with partial remission after three cycles of therapy.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…Nakatake and coworkers demonstrated in human cell lines that JAK2V617F alters p53 responses to DNA damage through upregulation of La antigen, which increases MDM2 protein translation. 24 We have recently reported that MDM2 levels are increased in primary PV CD34 1 cells, 13 whereas the p53 levels are reduced in CD34 1 cells from both patients with PV and PMF. The cis-imidazoline compounds termed nutlins were the first potent and selective MDM2 inhibitors, and their discovery stimulated widespread interest in the design of small molecule p53-MDM2 inhibitors.…”
Section: Introductionmentioning
confidence: 98%
“…Our laboratory has attempted to target the p53 pathway with pharmacologic agents with the hope of reducing or eliminating the numbers of MPN stem cells. 13 Because MPNs are likely the result of multiple genetic mutations as well as epigenetic events that are difficult to recapitulate in rodent models, we have used primary cells from MPN patients to evaluate these potential therapeutic agents. 13,14 The tumor suppressor p53 plays an important role in the control of DNA repair, the cell cycle, apoptosis, and cancer surveillance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation